Tingkat Kesepian dan Kepuasan Hidup Terhadap Tingkat Kebahagiaan Lansia yang Tinggal di Panti Werdha - Maria Manungkalit; Ni Putu Wulan Purnama Sari (Universitas Malahayati Lampung, 2023)
ABSTRACT Every individual will experience the aging process naturally which cannot be avoided. Elderly is someone who has entered the aging phase. Oftenly these people subjectively feel that they are no longer useful for their family and society. Sometimes they feel isolated from their social environment. Living in the nursing home may result in negative feelings to some extent. Thus, elderly feel lonely and unhappy, which may impact their life satisfaction. This study aimed to analyze the correlation between levels of loneliness and life satisfaction on the level of happiness in nursing home residents. This correlational study implemented cross-sectional design. The population was 150 elderly living in a private nursing home in Surabaya, Indonesia. The independent variables were the level of loneliness and life satisfaction which measured by instruments of UCLA loliness scale and Satisfaction with Life Scale (SWLS), respectively. The dependent variable was the level of happiness which measured by the Oxford Happiness Questionnaire (OHQ). Ordinal regression tests were employed in data analysis. The majority was old-aged individuals (75-90 y.o.), female, high school graduated, widowed, and closest to their children. The most frequent visit was done by their children. They live in the nursing home mainly due to the absence of caregiver at home. Currently, most respondents have been lived there for four years. High happiness was followed by mild loliness and very satisfied toward life in most respondents. There was a strong significant correlation between the level of satisfaction and happiness and between the level of loneliness and happiness with p value of 0.000 for each. Life satisfaction and loliness are strongly correlated with happiness in nursing home residents. Keywords: Elderly, Happiness, Loliness, Life Satisfaction, Nursing Home. ABSTRAK Setiap individu akan mengalami proses penuaan secara alami yang tidak dapat dihindari. Lansia merupakan seseorang yang telah memasuki fase menua. Seringkali orang-orang ini secara subjektif merasa dirinya tidak berguna lagi bagi keluarganya dan masyarakat. Terkadang mereka merasa terisolasi dari lingkungan sosialnya. Tinggal di panti jompo dapat menimbulkan perasaan negatif sampai batas tertentu. Dengan demikian, lansia merasa kesepian dan tidak bahagia, yang dapat berdampak pada kepuasan hidupnya. Penelitian ini bertujuan untuk menganalisis hubungan tingkat kesepian dan kepuasan hidup terhadap tingkat kebahagiaan penghuni panti jompo. Penelitian korelasional ini menggunakan desain cross-sectional. Populasinya adalah 150 lansia yang tinggal di salah satu panti jompo swasta di Surabaya, Indonesia. Variabel independennya adalah tingkat kesepian dan kepuasan hidup yang masing-masing diukur dengan instrumen skala kesepian UCLA dan Satisfaction with Life Scale (SWLS). Variabel terikatnya adalah tingkat kebahagiaan yang diukur dengan Oxford Happiness Questionnaire (OHQ). Uji regresi ordinal digunakan dalam analisis data. Mayoritas responden adalah lanjut usia tua (75-90 tahun), perempuan, lulusan SMA, janda, dan paling dekat dengan anak. Kunjungan paling sering dilakukan oleh anak-anak mereka. Alasan tinggal di panti jompo terutama karena tidak adanya pengasuh di rumah. Saat ini, sebagian besar responden telah tinggal di sana selama empat tahun. Kebahagiaan yang tinggi diikuti oleh rasa kesepian yang ringan dan sangat puas terhadap kehidupan pada mayoritas responden. Terdapat hubungan yang kuat dan signifikan antara tingkat kepuasan dan kebahagiaan serta antara tingkat kesepian dan kebahagiaan dengan nilai p masing-masing 0,000. Kepuasan hidup dan kesepian berhubungan kuat dengan kebahagiaan pada penghuni panti jompo. Kata Kunci: Lanjut Usia, Kebahagiaan, Kesepian, Kepuasan Hidup, Panti Jompo.